The role of family and peer factors in the development of early adolescent depressive symptoms: A latent class growth analysis - Zhang, Jiaying; Lin, Guangyao; Cai, Qiaole; Hu, Qian; Xu, Yuan; Guo, Zhaoming; Hong, Defan; Huang, Yingying; Lv, Yijun; Chen, Jing; Jiang, Suo (Frontiers in Psychiatry, 2022)
Few studies have explored the trajectories of Chinese early adolescent depressive symptoms or comprehensively considered the factors of family and peers. The present study aimed to identify the trajectories of depressive symptoms in early adolescence using a school-based sample assessed in three waves. The study also examined whether family and peer factors were significant predictors. A total of 586 Chinese primary and middle school students participated in the survey. A growth mixture model was used to find the trajectories of depressive symptoms, and multiple logistic regression was used to identify the predictors. Three trajectories were identified, including a stable-low class, an increasing class, and a high-decreasing class. Results indicated that gender, parental psychological aggression and neglect, parental psychological control, traditional/cyberbullying victimization, and friendship quality were significant predictors. However, witnessing intimate partner violence, parental behavior control, and traditional/cyberbullying perpetration could not significantly predict the trajectories. The findings of this study can provide an empirical basis for teachers and clinical interveners to determine different development trajectories of depressive symptoms and carry out prevention and intervention.